THE RELATIONSHIP AMONG POTENTIAL OF NATURAL RESOURCES, SOCIAL, ECONOMIC AND CULTURE OF COMMUNITIES INBUFFERZONE OF MOUNT HALIMUN NATIONAL PARK - Reni Sawitri; NM Heriyanto (BERITA BIOLOGI, 2001)
This study was conducted to know of potential of natural resources of Mt.Halimun used by surrounding communities and the development of bufferzone.The potential of natural resources are composed of wildlife, plant biodiversity,land and hydrology.Then, The utilization of natural resources will be correlated with the condition of socio economic and culture of communities.According to the study, it is known that the major occupation of the village communities are as farmers, who have private land or as laborers (>50%). As laborers, they worked for landlord with salary Rp. 5,000 to Rp 10,000 per day for six days per week. This condition made village communities to depend their livelihood to potential of natural resources of Mt. Halimun NP. Based on dynamic hypothesis,the bufferzone could be developed through data and information of the natural resources that utilized or disturbed by communities. The plant biodiversity are used as energy, traditional medicines, food, handicrafts and forages.Illegal hunting done by surrounding communities was hunting wild pigs, birds and monkeys.To limit the exploitation, illegal cutting, illegal hunting and deforestation The Mt Halimun NP have program social forestry and agroforestry to decrease dependency of communities to the forest. For example the sheep breeding with forage plants in bufferzone.Other programs such as goats breeding and fish or plants development could be done in border land of national park or private land of communities.